Toxicity Test of Cat Whiskers (Orthosiphon stamineus) and Miana (Coleus artropurpureus) Leaves Against Artemia salina Leach Using BSLT - Surahmaida (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Medicinal plants are a good source of therapeutic drugs because they contain phytochemical compounds. Cat's whiskers (Orthosiphon stamineus) and miana (Coleus artropurpureus) are plants that are widely used as herbal medicines. However, there are no studies related to toxicology to ensure its safety. The aim of this study was to determine the toxicity of 96% ethanol extract of cat whiskers and miana leaves to shrimp (Artemia salina Leach) larvae. Toxicity test was carried out using the Brine Shrimp Lethality Test (BSLT) method with 48 hours old Artemia salina shrimp larvae. The concentration of the extract used was 1 ppm, 2 ppm, 3 ppm, 4 ppm and 5 ppm. The results of the toxicity test showed that the 96% ethanol extract of cat's whiskers leaves had an LC50 value of 8.0855 ppm, while the 96% ethanol extract of miana leaves had an LC50 value of 4.7067 ppm. Based on the results of the study, it can be concluded that cat's whiskers and miana leaves have the potential to be developed as candidates for anticancer drugs.